Minimum damping profile of micro/nano-robot and as the carrier for drug delivery: theory study. (April 2019) - Yang, L X; Zhang, G C; Fan, N; Guo, J; Peng, B
Abstract: The use of the micro/nano-robot as a carrier for drug delivery in vivo represent a novel and innovative method in cancer/tumor therapy and related biomedical applications. In this paper, the authors firstly deduce the minimum damping profile of micro/nano-robot as it locomoting in vascular and capillaries system. Where originating from the Bernouli's equation, and integrating the calculus of variations with the Euler-Lagrange equation, then the profile of micro/nano-robot which the generatrix of this axisymmetric body is the 4/3 order of the curve is obtained. Following, the elastic responses of the cell indented by this profile are studied detailedly. Utilizing the method of continuum mechanics, the interior stress and displacement distributions, indentation depth, surface stress distribution (corresponding the critical rupture stress of cytomembrane) and applied force (corresponding the required force output from micro/nano-robot) are derived. Furthermore, those elastic responses indented by conical and spherical profile are computed and contrasted. Conclusively, the authors provide a design reference for the profile of micro/nano-robot as a carrier for drug delivery, and deduce the elastic responses of the cell when it penetrated by the body of micro/nano-robot.